2006
DOI: 10.1139/f06-074
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory inhibition and recovery in chum salmon (Oncorhynchus keta) following copper exposure

Abstract: Abstract:Copper can be an effective hatchery treatment to control certain parasitic and fungal infections in salmonids, yet it is also highly toxic to the fish's olfactory system. Numerous reports have described the early inhibitory impacts of copper on fish olfaction, but very few have addressed processes of recovery. Here we show that the chum salmon (Oncorhynchus keta) olfactory system can recover from short-term (4 h) exposures to copper (3-58 µgqL -1 ) within 1 day, as indicated by electro-olfactogram (EO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…In the wild, such changes can directly translate into increased vulnerability to predation or decreased food intake with possible consequences for growth and fecundity. For example, impairment of the olfactory function in salmon has been demonstrated after exposure to environmentally relevant concentrations of diazinon, an OP insecticide, and copper [39,40]. Copper concentrations of 2 mg/L, a concentration commonly detected in the Sacramento-San Joaquin Delta (I. Werner, unpublished data), completely eliminated the avoidance response of juvenile salmon to a predator cue.…”
Section: Discussionmentioning
confidence: 99%
“…In the wild, such changes can directly translate into increased vulnerability to predation or decreased food intake with possible consequences for growth and fecundity. For example, impairment of the olfactory function in salmon has been demonstrated after exposure to environmentally relevant concentrations of diazinon, an OP insecticide, and copper [39,40]. Copper concentrations of 2 mg/L, a concentration commonly detected in the Sacramento-San Joaquin Delta (I. Werner, unpublished data), completely eliminated the avoidance response of juvenile salmon to a predator cue.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of fish suggest that heavy metals directly damage sensing cells in the olfactory epithelium (e.g., Hansen et al 1999b), but in some cases fish that return to unpolluted conditions recover their olfactory function (e.g., Beyers and Farmer 2001;Baldwin et al 2003;Sandahl et al 2006), depending on the degree and extent of exposure to the metals. More recent research has revealed cases of lasting damage from short-term embryonic exposure.…”
Section: Mode Of Action Of Heavy Metalsmentioning
confidence: 99%
“…It is not clear to what extent the endocytosis observed in these experiments may be ligand specific. In a study on chum salmon, Oncorhynchus kisutch, whose olfactory epithelium was exposed to copper solutions, fluorescent styryl dyes (FM dyes) were used as membrane markers, and the authors concluded that the labelling of sensory neurons did not depend on the presence of an odorant (Sandahl et al, 2006).…”
Section: Introductionmentioning
confidence: 99%